Impacto del impuesto de renta y complementarios para las personas naturales a partir de la Ley 2277de 2022 en Colombia - Ropero Perez, Luis Fernando (Universidad Antonio Nariño, 2023)
This work seeks to answer the research question on the impact of income tax and complementary tax specifically on individuals as of Law 2277 of 2022, this tax is of great effect for the financing of the state, as of Law 2277 of 2022 a great economic impact on individuals is evidenced. The DIAN in recent years has been implementing better control systems in order to ensure the collection and the state must generate confidence and transparency with the investments made with tax resources.